Facilitative mediation as a sociocultural practice - Pokotylo, Elina (Ukrainian Cultural Studies, 2024)
Background. The current trend in conflict resolution emphasizes non-violent, less traumatic, and non-repressive communication. This approach focuses on halting destructive behaviours and fostering mutually beneficial solutions, with conflict resolution methods seen as a conscious effort shaped by value-based considerations. This shift aligns with the trend towards the 'democratisation' of fairness and recognition of individual autonomy in decision-making, as seen in the rise of mediation as an alternative dispute resolution method. This article examines the key characteristics of facilitative mediation as a specific practice of resource management at its current stage of development, drawing on the insights of mediators practising in the United Kingdom. A holistic approach is proposed, which considers the simultaneous functioning of role, emotional, temporal, and spatial structures within the practice.Methods. Interdisciplinary approach, comparative analysis, induction, deduction, generalisation, analysis, synthesis, and the descriptive method.Results. The dialogue in mediation is examined at individual, interpersonal, and intergroup levels. The functioning of attitudes, actions, positions, and interests in mediation process is explored. The study examines perspective-taking, social roles, informality, and the emotional structure of mediation, including emotional rules.Conclusions. Offline mediation is a unique form of mediation, as third party mediates the parties from each other with them co-present. Each of the studied structures has a specific dynamic pattern. Dialogue patterns are consistent across all communication levels. Mediation creates its own social reality with specific emotional rules. Emotions are regulated by temporal and spatial factors.
Keywords: mediation; facilitation; sociocultural practice; emotional structure; emotional rules; role structure; informality; spatial structure; temporal structure